Results of the molecular biology study of goat’s mange mites - T, Batnasan; U, Gantogtokh; P, Tserenlkham; Ch, Uuganbayar; D, Bayarmagnai; Sh, Tumenjargal; Ts, Erdene-Ochir; G, Nyamdavaa (Mongolian Journal of Agricultural Sciences, 2018)
Demodicosis, also called demodectic mange infests human and animals worldwide. It is a skin parasitic disease caused by demodex mites. Of 615 goats randomly selected from Central and Western regions of Mongolia were carried out to detect the demodectic mange by clinical examination. The prevalence of Demodicosis was 1.3% in goats. It was considered as suspected /diseased that the skin had multifocal nodules with grayish, dried rough surface which were approximately 3-9 mm in diameter. The encrusted lesions of skin, especially over face, necks, shoulder blades, groin and hair loss were found on selected Mongolian goats. The samples of skin scrapings from the goats with above clinical signs were collected. The mites were identified as Demodex spp by parasitological examination. DNA was extracted from positive samples. The specific genes (mt16s rDNA) of Demodex spp. was detected by PCR. The 16s rDNA fragment was sequenced and aligned. The presence of D.-caprae in Mongolian goats is confirmed by molecular biological study. Ямааны хамуу өвчнийг молекул биологийн түвшинд оношлосон дүн Хураангуй: Демодекоз нь хачгаар үүсгэгддэг, дэлхийд түгээмэл тархсан хүн, мал, амьтны арьсанд эмгэг нөлөө үзүүлдэг өвчин юм. Бид санамсаргүй түүврын аргаар Монгол орны баруун болон төвийн бүсийг төлөөлүүлэн нийт 615 толгой ямаанд демодекоз эмнэлзүйн үзлэг хийхэд 1.3 % нь демодекоз болон уг өвчний сэжигтэй байв. Өөрөөр хэлбэл, эрүү, шанаа, нүдний дээд, доод зовхи, хүзүү, дал, хонго, цавины арьсанд 0.3-0.9 см хэмжээтэй товхойсон барзгар гадаргуутай, арьсны зарим хэсэгт яршиж хогжруутсан, хуурайдуу, саарал өнгийн олон тооны гүврүүтэй, үс нь унасан шинж тэмдэгтэй ямааг өвчтэй, сэжигтэй гэж үнэлэв. Дээрх шинж тэмдэгтэй ямааны арьсны эмгэгтэй хэсгээс авсан дээж (хусдас)-д хийсэн шимэгч судлалын шинжилгээгээр Demodex төрлийн хачиг илрэв. Хачиг илэрсэн (эерэг) дээжнээс ДНХ-ийг ялгаж Полимеразын гинжин урвал (ПГУ)-аар шинжлэхэд mt 16S rDNA генийн хэсэг (339 хос суурь) илэрч Demodex төрлийн хачиг болох нь баталгаажив. Уг ДНХ-ийн нуклеотидын дарааллыг тогтоож, гений мэдээлэлтэй харьцуулахад бидний судалгаанд хамрагдсан Монгол ямаанд D.caprae зүйл хачиг шимэгчлэн демодекоз үүсгэснийг молекул биологийн түвшинд анх тутам тогтоосон болно. ТҮЛХҮҮР ҮГ: ПГУ, Demodex caprae, mt 16S rDNA, ямаа